Puncak Peradaban Profetik Masa Rasulullah saw; Periode Makkah dan Madinah - Basrah, Tahnia; Ramdhani , Mutiara (STAIN Majene, 2024)
The peak of prophetic civilization in Islamic history was reached during the leadership of the Prophet Muhammad SAW in the Mecca and Medina periods. The Mecca period was an early milestone in Islamic preaching which was marked by a heavy struggle against the oppression of the Quraysh. The migration to Medina marked a new chapter in the development of Islam. In Medina, Rasulullah SAW built a just and harmonious Islamic society. This article describes the development of prophetic civilization during the time of the Prophet Muhammad. in the Mecca and Medina periods. The method used in this research is descriptive analysis by referring to library sources, such as books, journals, historical books and articles related to the title of this article. The results of the research show that in the Mecca period the Prophet carried out more civilization related to faith and in Medina it was more developed and could be said to be the peak of civilization during the time of the Prophet. Puncak peradaban profetik dalam sejarah Islam tercapai pada masa kepemimpinan Nabi Muhammad SAW di periode Makkah dan Madinah. Periode Makkah menjadi tonggak awal dakwah Islam yang diwarnai dengan perjuangan berat menghadapi penindasan kaum Quraisy. Hijrah ke Madinah menandai babak baru dalam perkembangan Islam. Di Madinah, Rasulullah SAW membangun tatanan masyarakat Islam yang adil dan harmonis. Artikel ini memaparkan perkembangan peradaban profetik pada masa Rasulullah saw. pada periode Makkah dan Madinah. Metode yang digunakan dalam penelitian ini adalah analisis deskriptif dengan merujuk pada sumber pustaka, seperti buku-buku, jurnal, kitab-kitab sejarah serta artikel yang berkaitan dengan judul artikel ini. Hasil penelitian menunjukkan bahwa Pada periode Makkah Rasulullah lebih banyak melakukan peradaban terkait akidah dan di Madinah sudah lebih berkembang dan bisa dikatakan sebagai puncak peradaban pada masa Rasulullah saw.